VISUAL OUTCOME BETWEEN EARLY AND DELAYED VITRECTOMY IN ENDOPHTHALMITIS PATIENTS OPERATED IN KARIADI GENERAL HOSPITAL, SEMARANG : TWO YEARS DESCRIPTIVE STUDY: Oral Presentation - Observational Research - Resident - Rahmayanti, Suci; Pragnanda, Satya Hutama (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesEndophthalmitis is a medical emergency caused by infection of tissue or fluids inside the eyeball.Vitrectomy for endophthalmitis is one of the treatment choice and leads to VA gains in some cases.Timing of surgery and visual outcome after surgery are vital to acknowledge. This study aims toanalyze the difference of visual outcome between early and delayed vitrectomy in endophthalmitispatients operated in Dr. Kariadi General Hospital MethodsA Retrospective study held from medical record of patients with endophthalmitis underwentvitrectomy surgery from January 2021 – January 2023 in Dr. Kariadi General Hospital, Semarang.Endophthalmitis patients caused by trauma were excluded. All of the patients had immediatevitrectomy, and based on duration of symptoms, the patients were divided into two groups, earlyvitrectomy (duration of symptoms ? 7 days) and delayed vitrectomy (duration of symptoms > 7days). Independent t- test method was used to analyze the data (significant if p<0.05) ResultsTotally 30 endophthalmitis patients (30 eyes) were obtained. There were 18 patients (60%) had earlyvitrectomy and 12 patients (40%) had delayed vitrectomy. Postoperative examination showed 13(72%) patients with early vitrectomy had improved VA, and 5 (28%) had constant VA. On the otherhand, patients with delayed vitrectomy showed 5 (42%) had improved VA, 6 (50%) had constant VA,and 1 (8%) had decreased VA. The difference between two groups was significant (p=0.014) ConclusionThis study found endophthalmitis patients with early vitrectomy had significant better visualoutcome than delayed vitrectomy